2005
DOI: 10.1089/dna.2005.24.438
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Muscle Myosin II Promotes Sensory Axon Formation

Abstract: Myosin II is an intracellular force-generating enzyme with no known extracellular action. In the course of experiments involving trituration loading of skeletal myosin II into embryonic sensory neurons we observed that extracellular application of myosin II to neurons resulted in a robust increase in the number of axons initiated by each neuron, but did not alter the rate of axon extension. Substratum bound myosin II in the presence of laminin was sufficient to elicit increases in axon formation. However, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Cell attachment assays were performed as previously described (Silver and Gallo, 2005) and the number of attached neurons was determined by staining coverslips with neuron-specific bIII tubulin antibodies. Briefly, cells were plated in parallel on coverslips coated with laminin or polylysine for 3.5 h. The medium was then removed and the coverslips were washed three times to remove nonadherent cells by adding and removing 1 mL of fresh culture medium, allowing the medium to run over the coverslip.…”
Section: Cell Attachment Assaymentioning
confidence: 99%
“…Cell attachment assays were performed as previously described (Silver and Gallo, 2005) and the number of attached neurons was determined by staining coverslips with neuron-specific bIII tubulin antibodies. Briefly, cells were plated in parallel on coverslips coated with laminin or polylysine for 3.5 h. The medium was then removed and the coverslips were washed three times to remove nonadherent cells by adding and removing 1 mL of fresh culture medium, allowing the medium to run over the coverslip.…”
Section: Cell Attachment Assaymentioning
confidence: 99%
“…Peripheral nerve recovery after crush injury was suppressed by chronic inflammation in peripheral target tissue [11]. Extracellular application of myosin II or skeletal muscle extract to neurons resulted in a robust increase in the number of axons initiated by each neuron or the number of survival neurons [12][13]. Sensory nerve cross-anastomosis (sensory protection) provides a modified trophic environment by modulating neurotrophic factor synthesis in muscle [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sensory neurons lost in the absence of target‐derived trophic support should be rescued by treatment with muscle extract or neurotrophic factors which are known to be required for the survival of these neurons (Snider,1994; Caldero et al,1998). Extracellular application of skeletal myosin II to embryonic sensory neurons resulted in increasing axon formation and branching in each neuron in vitro (Silver and Gallo,2005). It has been shown that the increase in excitability of skeletal muscle is regulated by the excitatory afferents in the spinal cord‐DRG‐skeletal muscle organotypic coculture system (Streit et al,1991).…”
mentioning
confidence: 99%